2004
DOI: 10.1111/j.1601-5223.2003.01763.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and molecular characterization of Aethomys kaiseri from Zambia and Aethomys chrysophilus from Tanzania (Rodentia, Muridae)

Abstract: Aethomys is a common and widespread rodent genus in the African savannas and grasslands. However, its systematics and taxonomy are still unclear as no study has covered the entire range. In fact it might not be a monophyletic genus and perhaps should be split into two subgenera, Micaelamys and Aethomys. In this paper, we present findings based on the cytogenetics and the entire cytochrome b sequence of two species from Zambia (A. kaiseri ) and Tanzania (A. chrysophilus), and we compare them with the sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For the species distribution modeling, we merged all georeferenced records of the Aethomys chrysophilus complex from our own and published data sets (Gordon and Rautenbach 1980, Gordon and Watson 1986, Visser and Robinson 1986, 1987, Baker et al 1988, Breed et al 1988, Ducroz et al 2001, Fadda et al 2001, Castiglia et al 2003, Linzey et al 2003, Russo et al 2006, Nicolas et al 2011, Phukuntsi et al 2016, this study) in which species identity was confirmed by mtDNA, karyotypes and sperm morphology (see Supplemental File 1). After discarding samples from identical localities and rounding latitudes and longitudes to 0.5° we obtained 126 unique records.…”
Section: Species Distribution Modelingmentioning
confidence: 99%
“…For the species distribution modeling, we merged all georeferenced records of the Aethomys chrysophilus complex from our own and published data sets (Gordon and Rautenbach 1980, Gordon and Watson 1986, Visser and Robinson 1986, 1987, Baker et al 1988, Breed et al 1988, Ducroz et al 2001, Fadda et al 2001, Castiglia et al 2003, Linzey et al 2003, Russo et al 2006, Nicolas et al 2011, Phukuntsi et al 2016, this study) in which species identity was confirmed by mtDNA, karyotypes and sperm morphology (see Supplemental File 1). After discarding samples from identical localities and rounding latitudes and longitudes to 0.5° we obtained 126 unique records.…”
Section: Species Distribution Modelingmentioning
confidence: 99%
“…The genus Aethomys Thomas, 1915 was formerly subdivided into two African endemic subgenera namely Micaelamys and Aethomys [2]. Recent molecular studies [19,29,30] reported the paraphyly of the genus and the two subgenera have since been elevated to full generic rank [2]. The genus Micaelamys Ellerman, 1941 includes M. namaquensis and M. granti Wroughton, 1908, while Aethomys includes the remaining nine species.…”
Section: Introductionmentioning
confidence: 99%
“…Chidumayo 1977, 1979, 1980a, b, 1984, Kawalika 2004) and a few individuals from Zambia were also used as a part of recent systematic reviews of some taxonomic groups (e.g. Burda et al 1999, Castiglia et al 2002, Castiglia et al 2003, Corti et al 2004, 2005, Mullin et al 2004, 2005, Carleton & Stanley 2005, Taylor et al 2009. The lack of systematic research of Zambian rodents in the last 40 years has led to the absence of up-to-date patterns of distribution of rodent species, especially in the taxonomically complicated groups, where the genetic approaches recently led to the description of many new cryptic species (e.g.…”
Section: Introductionmentioning
confidence: 99%